Analysis of Factors Related to Organizational Citizenship Behavior in Health Care Workers - Grace Tedy Tulak; Yuhanah Yuhanah; Iis Afrianty; Harni Sartika Kamaruddin; Sihnith SAY (PT.Mantaya Idea Batara, 2026)
Introduction: Organizational Citizenship Behavior (OCB) is a choice behavior that is not part of an employee's formal work obligations. OCB is reflected in employees who help fellow employees with extra workloads and who comply with existing workplace regulations and policies. Many factors can shape OCB, including age, length of service, job satisfaction, and organizational commitment. This study aims to analyze factors related to organizational citizenship behavior. The research design used in this study is descriptive-analytical with a cross-sectional study approach. The sampling method in this study was purposive, so the number of respondents was 108. The research instrument used was a questionnaire. The data was analyzed using univariate and bivariate Spearman's rho. There is a moderate positivecorrelation (0.42), indicating that older officers tend to show higher OCB, butthe relationship is insignificant (p = 0.679). There is a moderate positive correlation (0.42), indicating that officers with longer work experience are more involved in OCB, but the relationship is not statistically significant (p = 0.679). The strong positive correlation (0.60) indicates that job satisfaction can create high OCB, and p = 0.001 indicates a significant relationship. There is a low negative correlation (-0.203), indicating that high organizational commitment can reduce OCB; p = 0.042 indicates a significant relationship. Age and years of work experience do not have a significant relationship with OCB, whereas job satisfaction and organizational commitment do in health workers.